Multifunctional hybrid porous filters with hierarchical structures for simultaneous removal of indoor VOCs, dusts and microorganisms. Issue 17 (23rd February 2017) - Zhao, Yang; Low, Ze-Xian; Feng, Shasha; Zhong, Zhaoxiang; Wang, Yong; Yao, Zhong
Abstract : Air purification often requires multiple layers of filters with different functions to remove various air pollutants, which lead to high pressure drop, high air flow path and frequent filter replacement. Abstract : Air purification often requires multiple layers of filters with different functions to remove various air pollutants, which lead to high pressure drop, high air flow path and frequent filter replacement. In this work, a novel multifunctional Ag@MWCNTs/Al2 O3 hybrid filter with a depth-type hierarchical structure for simultaneous removal of fine particles, microorganisms and VOCs was designed and fabricated. The novel hybrid air filter showed leading air purification performances to date, achieving 82.24% degradation of formaldehyde at room temperature, 99.99% formaldehyde degradation at 55 °C and complete retention of indoor airborne microorganisms. The complete particle retention rate (100% retention) based on the most penetrating particle size (MPPS, aerodynamic diameter ≦300 nm) of Ag@MWCNTs/Al2 O3 was achieved at an only 35.60% pressure drop compared with the pristine Al2 O3 filter, leading to the highest quality factor ( Q f ) ever reported. Furthermore, the Ag@MWCNTs/Al2 O3 hybrid filter showed excellent water repellency (water contact angle of 139.6 ± 2.9°), prolonging the service life of the filters and improving the air purification efficiency. The novel Ag@MWCNTs/Al2 O3 hybrid filter exhibits remarkable air purification performance in both laboratory synthetic conditions as well as in the "real world" and shows great promise as an effective single replacement for multiple layers of air purifying filters.